Prevalence of bullying in the nursing workplace and determinant factors: a nationwide cross-sectional Polish study survey - Bozena Czarkowska-Paczek; Lena Izabela Serafin (BMJ Open)
Objectives In the present study, we aimed to investigate the prevalence of bullying among Polish nurses, and to identify the most common negative acts, as well as individual and work-related risk factors for workplace bullying.Methods Cross-sectional study designed using an online survey. The total study sample was 404 nurses, each having over 6 months of working experience. Data were collected using the Polish version of the Negative Act Questionnaire-Revised. Linear stepwise regression analysis and logistic regression analysis were performed to assess predictors of greater reporting of perceived workplace bullyingResults Bullying was experienced by 65.84% of participants. Perceived workplace bullying was associated with sex (p=0.043), age (p=0.003), seniority (p=0.006), number of working hours per week (p=0.010) and position (p=0.029). Logistic regression analysis with the dependent variable of bullying according to Leymann’s rigorous criteria revealed that the model could include four variables: age from 50 to 59, seniority of 11–15 years,>45 working hours per week and a bachelor’s degree in nursing.Conclusions An alarming percentage of nurses were victims of bullying. Among all variables included in the regression model, the most significant predictors of perceived workplace bullying were age, seniority, work overtime and bachelor’s degree education. Bullying prevention and improvement of well-being at work must be addressed as part of an overall strategy to deal with turnover.